Empirical and theoretical considerations toward a model for caribou socioecology - Davis, James L.; Valkenburg, Patrick; Boertje, Rodney D. (Rangifer, 1986)
The Delta and Yanert caribou (Rangifer tarandus granti) herds apparently maintained discrete calving areas from 1979 through 1983 (as determined by radio telemetry studies), even though substantial intermixing occurred during other seasons. Also, the Delta herd apparently used a single traditional calving area from the 1950's through 1983, based on results of aerial surveys and 1979-83 telemetry studies. Calving distribution in 1984 changed dramatically; 5 of 25 radio-collared Delta herd cows ^3 years old and 5 of 24 radio-collared Delta herd cows
Keywords: calving; caribou; conceptual model; dispersal; herd identity; socioecology